TREATMENT OF UNCOMPLICATED DENTAL CARIES OF DECIDUOUS TEETH PROVIDING GENERAL ANESTHESIA FOR CHILDREN OF SCHOOL AGE - Koval, O.I. (World of Medicine and Biology, 2019)
The purpose of the present study was to substantiate the amount and sequence of dental manipulations for the treatment of uncomplicated deciduous teeth caries providing general anesthesia for children of school age. A comparative analysis of the deciduous teeth uncomplicated caries treatment results was performed in children aged 6 to 18 years, who had been treated according to the suggested scheme, under general anesthesia and standard charts on an outpatient basis. Over 2 year after the sanitation of oral cavity for children of school age, carried out under the conditions of a general anesthesia, complications of caries arose about in 15,67% of cases, mainly in the teeth with a presence of medium and deep caries in its acute course. Assessment of the treatment efficacy, carried out 2 years later, gives evidence for sufficiently high efficacy of the suggested manipulations and it seems advisable to recommend it for general use in dental practice.